Economic Transformation: The New Spiritual Leadership Model In Blimbingsari Village Jembrana Bali - Wayan Junaedi; Dermawan Waruwu (Yayasan Riset dan Pengembangan Intelektual, 2020)
A spiritual leader can appear in any situation. It can not be just a genetic theory that allows a person to be a spiritual leader but is supported by social theory and ecological theory. In addition to the above theory, there is one more the most fundamental theory of the emergence of a spiritual leader of Divine theory. The aim of this study is to identify the meaning of spiritual leadership in Blimbingsari Village, to identify the principle of spiritual leadership in Blimbingsari Village, and to analyze what does the spiritual Leader do to the economic transformation of Blimbingsari village. The methodology used is qualitative with data collection techniques are participant observation or participatory nature of direct involvement, interview, literature review, case study, and documentation. Village leaders Blimbingsari always increase leadership capacity through the intervention of the factors of spiritual values, work ethics, social capital, and entrepreneurial factors. These factors are growing in the middle of the village of Blimbingsari understood as a pattern of beliefs, values, and behaviors and leaders as agents of change do the role and relationship with the community intensive because it is influenced by historical trends, social attitudes, and socioeconomic factors.